Advertising / What It is and How to Do It - White Roderick (Mcgraw Hill Book Company, 1980)
A practical guide for anyone about to get involved in the world of advertising. Foreword, Acknowledgements, Introduction, Should You Advertise: and if so how much?, Do I Need an Agency?, The Marriage Business, Meet the Agency, How Advertising Works, Planning Advertisements, Creating Ads, How to Judge Advertisements, Media: Where the Ideas Can Be Seen, Television, Press Media, The Minor Media, Production for Print Media, Getting it Together - Planning the Campaign, Advertising and the Law, Advertising and Society, Advertising and Economics, International and Multinational and Global Advertising: Why?, The Future: Where Do we All Go from Here?, Further Sources of Information, Index.